Permainan Tradisional Berbasis Budaya Melayu dalam Pengembangan Karakter Anak - Adolf Bastian; Suharni; Yesi Novitasari (Institut Agama Islam Negeri Langsa, 2019)
This study aims to develop the character of early childhood by using cultural malay-based traditional games. The children's world is synonymous with the playing world so that learning is more easily absorbed by children through play. Traditional games are very important to be introduced so children can find out games that have been around for generations. Children are introduced to traditional games that elevate Malay culture. The Malay culture is a characteristic of the Lancang Kuning earth, so that it became the Riau Vision and Mission in building its territory in reference to Malay Culture. In addition, through Malay culture children are educated in character building. The character of children is shaped according to Malay culture which is full of morality and religion. Child character development is very important to be formed early because character is permanent and inherent in children to adulthood. This study belongs to the category of descriptive research which describes the data relating to the formulation of the problems examined in this study. Data collection used in this study was carried out by total sampling technique. This research uses a Likert scale, namely from the results of observations and interviews. Then, the data analysis technique used is descriptive technique.